Tubular strength comparison of offshore jacket structures under API RP2A and ISO 19902 - Arazi, Idrus, Assoc. Prof.; Narayanan Sambu Potty, Assoc. Prof.; Zafarullah, Nizamani (The Institution of Engineers, Malaysia (IEM), 2012)
Link to publisher's homepage at http://www.myiem.org.my/